The gospel behind the Gospels : current studies on Q - Piper, Ronald A. 1948- (Novum Testamentum, Supplements, 1995)
The Gospel Behind the Gospels portrays all the major areas of current discussion and debate regarding the early source of Jesus' sayings known as Q. Sixteen gospel scholars have advanced the debate about this source's nature, history and significance. Contributors discuss Q's existence, its relationship to Mark's gospel and to the Gospel of Thomas, its genre, its redactional history with special reference to the Son of Man and to wisdom and prophetic traditions, its social history with respect to family structures and the Cynics, a feminist analysis of Q, its significance for the historical Jesus and for Jesus' parables. The volume sheds important light on Jesus and Christian origins as well as upon Q itself, and it is significant for the diversity of major North American, European and Japanese scholarship which is represented.